Epidemiological perspectives on emerging contaminants and gout or hyperuricemia - Weiwen Fu; Yangyi Guang; Zixing Zhang; Cheng Zhou; Xinyu Fang (Emerging Contaminants)
Recently, there has been a global rise in the burden of hyperuricemia and gout, attributed to socio-economic development and rapid urbanization. Emerging contaminants (ECs), associated with industrialization, including endocrine-disrupting chemicals (EDCs), persistent organic pollutants (POPs), pesticides, heavy metals, and microplastics (MPs). These contaminants may potentially exacerbate the prevalence and incidence of hyperuricemia and gout through various pathways. In this review, we outline the recent epidemiologic studies between ECs and hyperuricemia and gout and discuss the common exposure pathways of ECs, aiming to inform strategies for reducing exposure and mitigating future health impacts.